2010
DOI: 10.4014/jmb.1003.03041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glasswort (Salicornia herbacea L.) on Microbial Community Variations in the Vinegar-making Process and Vinegar Characteristics

Abstract: Three types of nuruk were made from rice, wheat, and a rice-glasswort (6:4) mixture. Nuruk, makgeolli, and vinegar were manufactured with rice nuruk (RN), wheat nuruk (WN), and rice-glasswort nuruk (RGN). The variable region of 18S or 16S rDNA amplified with genomic DNA extracted directly from nuruk-, makgeolli-, and vinegarmaking cultures was analyzed via temperature gradient gel electrophoresis (TGGE). The sequence of the 18S rDNA variable region extracted from the TGGE gel for nuruk was 99% homologous with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Its consumption has been actively encouraged because of its overproduction in Korea. Rice has long been a very popular material for processed and fermented foods including cake, syrup, sweet drinks, cookies, vinegar, and makgeolli [10,11]. Especially, rice has been used as a main material with hot pepper and meju in the preparation of gochujang (Korean red pepper paste), in which rice is used as carbohydrate source for fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Its consumption has been actively encouraged because of its overproduction in Korea. Rice has long been a very popular material for processed and fermented foods including cake, syrup, sweet drinks, cookies, vinegar, and makgeolli [10,11]. Especially, rice has been used as a main material with hot pepper and meju in the preparation of gochujang (Korean red pepper paste), in which rice is used as carbohydrate source for fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…In India, shoots can also be transformed into beverages such as nuruk (fermentation starter), makgeolli (Korean rice wine), or vinegar [82,83]. One study found that Salicornia enhances fermenting microbe propagation and improves vinegar quality [84]. Other authors have found that these plants can be used as a source of salt for several dishes.…”
Section: Discussionmentioning
confidence: 99%
“…Other minerals contained in dried glasswort except NaCl are preserved mostly after the NaCl is washed out [3,6]. In previous research, dried glasswort flake has been used as a subsidiary material to prepare nuruk and meju, whereas makgeolli and vinegar are prepared with nuruk by fermentation, and kanjang has been extracted from meju by long-term ripening [7,8].…”
Section: Introduction mentioning
confidence: 99%